Over-expression of CRTH2 indicates eosinophilic inflammation and poor prognosis in recurrent nasal polyps - Chen, Wenhui; He, Shaojuan; Xie, Xinyu; Yang, Xiaorong; Duan, Chen; Ye, Ping; Li, Xuezhong; Lawrence, Monica G.; Borish, Larry; Feng, Xin (Frontiers in Immunology, 2022)
Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is often characterized by recurrent nasal polyp (NP) growth following surgical removal, but the mechanisms are still not clear. This study aimed to investigate the expression of chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2) receptor on NP and the role it plays in eosinophil inflammation and polyp recurrence. Methods: Forty-one CRSwNPs patients and seventeen controls were enrolled in this study. mRNA was extracted from nasal tissues and evaluated for expression of CRTH2. Immunofluorescence staining was performed to confirm the distribution and expression of CRTH2 protein. CRTH2 expression on peripheral blood eosinophils was quantified by flow cytometry. The eosinophil count and clinical implications were also evaluated and their correlations with CRTH2 expression were analyzed. Results: Nasal polyps displayed increased expression of CRTH2 in mRNA level compared with control samples, with the highest expression observed in recurrent NP. Immunofluorescence confirmed over-expression of CRTH2 in recurrent NP and this was independent of the concurrent presence of asthma. CRTH2 expression was positively correlated with tissue eosinophil number (Spearman's ρ=0.69, P<0.001) and the postoperative sino-nasal outcome test-22 (SNOT-22) score (Spearman's ρ=0.67, P<0.001). Receiver operating characteristic (ROC) curves revealed CRTH2 was more predictive for NP recurrence compared to either eosinophil number and concomitant asthma, with an area under the ROC curve of 0.9107. Conclusion: The over-expression of CRTH2 in recurrent nasal polyps correlates with greater eosinophilic inflammation and poor prognosis which is independent of concomitant asthma.